2016
DOI: 10.1080/00365513.2016.1230886
|View full text |Cite
|
Sign up to set email alerts
|

The variation in high sensitive cardiac troponin concentration during haemodialysis treatment is not similar to the biological variation observed in stable end stage renal disease patients

Abstract: The CV and CV are similar to earlier findings. Mean hs-cTn concentrations decreased during HD. The within-subject hs-cTn variation during HD is similar to the between-subject variation, i.e. determining a cut-off value for hs-cTn changes during HD may be useful.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
11
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(15 citation statements)
references
References 41 publications
2
11
2
Order By: Relevance
“…The median pre-dialysis hsTnI levels in asymptomatic HD patients reported in previous studies were 13–25 ng/L (Table 3)[14,16,17,19]. The present study had the median pre-dialysis hsTnI levels of 54.3 ng/L (20.6–152.7).…”
Section: Discussionsupporting
confidence: 46%
See 2 more Smart Citations
“…The median pre-dialysis hsTnI levels in asymptomatic HD patients reported in previous studies were 13–25 ng/L (Table 3)[14,16,17,19]. The present study had the median pre-dialysis hsTnI levels of 54.3 ng/L (20.6–152.7).…”
Section: Discussionsupporting
confidence: 46%
“…The effect of HD on hsTnI levels are unestablished, reporting either increasing [17], unchanged [14,18] or decreasing of post-dialysis hsTnI levels (Table 3) [19,24]. The present study demonstrated that dialysis process affected the levels of hsTnI.…”
Section: Discussionmentioning
confidence: 56%
See 1 more Smart Citation
“…Current understanding of cTn variability is insufficient in these cohorts, as relatively few studies have been performed in individuals with renal or cardiac disease, as summarised in Table 2 and Table 3 respectively. 36,37,[71][72][73]75,[81][82][83][84][85] Interestingly, the biological variability of cTn has been found to be fairly similar between healthy individuals and individuals requiring dialysis. 36,71,73 Furthermore, the biological variability of cTn in individuals with stable coronary artery disease or cardiac failure has also been found to be comparable to that in healthy individuals.…”
Section: Biological Variation Results From Previous Studiesmentioning
confidence: 99%
“…The results revealed a need to identify optimal cut-off points of troponins for patients with CKD and ACS for proper risk stratification. Aligned with these conclusions is the study performed by Skadberg et al [21]. The author measured, using hs-Tn assays, troponin levels before and after hemodialysis and found that mean values decreased during this process.…”
Section: Chronic Kidney Diseasementioning
confidence: 85%